The Marvellers - Clayton, Dhonielle (Clayton, Dhonielle. Conjureverse, 2022)
Eleven-year-old Ella Durand is the first Conjuror to attend the Arcanum Training Institute, a magic school in the clouds where Marvellers from around the world practice their cultural arts, and she soon learns that fitting in is harder than it looks as some Marvellers mistrust the magic of Conjurors. Fortunately, she becomes friend with elixirs teacher, Masterji Thakur, and students Brigit and Jason. But things go from bad to worse when a dangerous criminal known as the Ace of Anarchy escapes prison, supposedly with a Conjuror's aid, and Masterji Thakur goes missing. Ella embarks on a mission with Jason and Brigit to find her mentor and find a way to clear her peoples' name.